A haptic‐enabled novel approach to cardiovascular visualization. (16th May 2014) - Yasmin, Shamima; Du, Nan; Chen, James; Feng, Yusheng
ABSTRACT Intravascular ultra sound (IVUS) imaging technique is widely used for the detection of plaque deposit inside coronary artery wall. Adequate detection of plaque deposit is necessary for further treatment of the patient, but image by image analysis, nevertheless, is cumbersome. In this paper, we proposed a fully automatic novel method for coronary artery visualization, which takes as an input a number of intravascular ultrasound images to construct the 3D model of coronary artery wall where the plaque deposit is demarcated in a rapid 3D rendering environment. This 3D visualization of coronary artery model has been enhanced in a haptic environment where the user is not only able to visualize the fatty plaque deposit but is also able to feel and differentiate stiffness of plaque deposit as well as soft, elastic property of normal artery through a virtual tour along the artery pathway. Copyright © 2014 John Wiley & Sons, Ltd.